The Effectiveness of Different Teaching Methods According to the Kolb Theory in Performance Accuracy of Some Basic Skills and Neuralgic Inhibition in Tennis - Aqeel Yahya Hashim Abdulaziz; Zainab Nadhim Shakir Al. Gburi (Journal of Global Pharma Technology, 2017)
In an attempt to use modern techniques in learning skills and believing that there is a need to re-examine the method used and provide the potential for the student to obtain information from them to ensure the process of education and to change the methods that are widespread based on memorization and conservation and literal application and replace them with modern methods to ensure the development of thinking and creativity capabilities of teachers and students And to benefit from modern information and techniques , And experimenting through the effectiveness of different teaching methods in accordance with the patterns of the theory of the circle Kolb in the performance of the accuracy of some basic skills in tennis. The aim of the research was to identify the classification of students according to the Kolb theory and the different teaching methods suitable for each classification, and to identify the best groups that were used according to Kolb's theory of performing some basic skills in tennis. The researchers hypothesized that the use of various teaching methods according to "Kolb theory is positively effective in learning some basic skills in tennis. he fields of research were the human field: students of the Department of Physical Education and Sports Sciences - Faculty of Education for Girls - University of Kufa, class III / for the academic year (2016 - 2017) .The period field from 1/11/2016 until 1/8/2017, and the spatial field ,in the internal gymnasium of the department of Physical Education and Sports Sciences - Faculty of Education for Girls - University of Kufa . The researchers used the experimental method in the two groups (experimental) method. On this basis, the researchers selected the sample of the students from the third stage of the Department of Physical Education and Sports Sciences / Faculty of Education for Girls / University of Kufa with (25). After excluding (7) female students from the original society for their participation in the exploratory experiment, the sample was selected by 18 female students in the simple random way , Which was divided into two experimental groups according to the classification form of the theory of Kolb, which classified the sample to the practical and theoretical and according to the qualifications of each student, the first experimental group (the practical) (10) students and applied the method of solving problems in teaching basic skills in tennis , And the second experimental group (theorists) (8) students. The method of mental training in teaching was applied to the basic skills of the tennis game. The special units were prepared for each group after presentation to the experts and the preparation of the tools for experimental procedures such as computer use , video clips and strips educational, rackets and tennis balls, and form evaluating the performance of accuracy, was applied (8) educational units on the two sets of research experimental, by one unit for each week, as it has been implementing the teaching style of solving problems with the first experimental group (practically) and the style of mental training with the second experimental group (theorists), and the conclusions obtained between the results of tribal tests and dimensionality and there is a significant moral differences and in the interest posteriori tests and both sets, and either posteriori tests results were the absence of significant differences between the two groups differences The pilot, and the researchers recommended that the need to use Kolb's theory circle in teaching. Keyword: Methods and methods of teaching, Kolb theory, Learning patterns, Tennis and precision performance.